Videodermoscopy in the Assessment of Patients with Ocular Demodicosis - Sławińska, Martyna; Jaworska, Karolina; Wyszomirski, Adam; Rychlik, Katarzyna; Nowicki, Roman J.; Sobjanek, Michał (Dermatology Practical & Conceptual, 2023)
Introduction: There is growing evidence of the potential uses of dermoscopy in diagnostics of demodicosis. No previous studies have analyzed dermoscopic features in patients with ocular demodicosis. Objectives: To evaluate the potential usefulness of videodermoscopy in diagnostics of ocular demodicosis. Methods: It was a single-center prospective observational study in which results of videodermoscopic examination of the eyelids were compared to the results of classic microscopic examination in patients with suspected ocular demodicosis and healthy volunteers. Results: Study group included 16 women and 15 men. In fifteen (48.4%) patients, microbiological examination of epilated eyelashes was positive. The results of forms filled by the patients concerning known subjective clinical symptoms of ocular demodicosis revealed no significant differences between the group with positive and negative results of microscopic examination. The presence of Demodex tails and madarosis observed during dermoscopic assessment correlated positively with positive results of microscopic examination. At least one Demodex tail was found in 86.7% (13/15) cases with positive results of microscopic examination. In the two remaining cases microscopic evaluation showed the presence of Demodex brevis. In 37.5% (6/16) of patients with negative results of microscopic examination, videodermoscopy showed the presence of Demodex tails. Conclusions: Videodermoscopy may facilitate the diagnostics of ocular demodicosis. Patients reporting clinical symptoms suggesting ocular demodicosis but negative results of videodermoscopic examination should be referred to classical microscopic examination to exclude the presence of Demodex brevis. In patients with negative microscopic examination results and symptoms suggesting ocular demodicosis, dermoscopy-guided microscopic re-evaluation could be considered.